Tantangan dan Solusi Pendanaan Lembaga PAUD: Ketergantungan Iuran Orang Tua dan Minimnya Dukungan Eksternal - Thesa Monica; Ismaniar Ismaniar; Lili Dasa Putri (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This article analyzes the challenges and solutions surrounding funding for Early Childhood Education (ECE) institutions in Indonesia, with a particular focus on the high dependence on parental fees and the limited availability of external support. ECE plays a crucial role in supporting children’s development during their early years; however, many institutions struggle with financial instability due to inadequate and inconsistent funding sources. This study uses a literature review approach by synthesizing relevant books, journal articles, government regulations, and institutional reports to provide a comprehensive understanding of the funding landscape. Findings show that most ECE institutions rely heavily on parental contributions, causing financial vulnerability, limiting program development, and reducing access for low-income families. Government assistance through the Operational Education Assistance (BOP) remains insufficient and often delayed. Meanwhile, collaborations with the private sector, CSR programs, and community-based support are still minimal. Financial challenges negatively affect institutions’ ability to provide adequate facilities, ensure teacher welfare, and implement holistic-integrative learning programs. The study suggests several solutions, including strengthening financial management capacity, applying participatory budgeting, diversifying funding sources, and initiating creative economic programs such as school bazaars and community partnerships. These strategies are expected to improve sustainability and enhance the quality of ECE services in Indonesia.